2020
DOI: 10.3389/fphys.2020.583393
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Cellular Functions of MG53 in Muscle Calcium Signaling and Regeneration

Abstract: Since its identification in 2009, multiple studies have indicated the importance of MG53 in muscle physiology. The protein is produced in striated muscles but has physiologic implications reaching beyond the confines of striated muscles. Roles in muscle regeneration, calcium homeostasis, excitation-contraction coupling, myogenesis, and the mitochondria highlight the protein's wide-reaching impact. Numerous therapeutic applications could potentially emerge from these physiologic roles. This review summarizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…It may be anticipated that, similar to the liver, other organs could also release proteins capable of modifying insulin receptor activation, finally leading to changes in metabolic performance. A potential candidate is mitsugumin 53 (MG53), a muscle-specific protein with multiple functions including muscle regeneration, calcium homeostasis, excitationcontraction coupling, and myogenesis [26]. In 2013, it was reported that MG53 is upregulated in models of insulin resistance and that it modifies insulin signaling by targeting the degradation of the insulin receptor β-subunit and of IRS1 by its ubiquitin E3 ligase activity [27].…”
Section: Inhibitory Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be anticipated that, similar to the liver, other organs could also release proteins capable of modifying insulin receptor activation, finally leading to changes in metabolic performance. A potential candidate is mitsugumin 53 (MG53), a muscle-specific protein with multiple functions including muscle regeneration, calcium homeostasis, excitationcontraction coupling, and myogenesis [26]. In 2013, it was reported that MG53 is upregulated in models of insulin resistance and that it modifies insulin signaling by targeting the degradation of the insulin receptor β-subunit and of IRS1 by its ubiquitin E3 ligase activity [27].…”
Section: Inhibitory Modulatorsmentioning
confidence: 99%
“…In 2013, it was reported that MG53 is upregulated in models of insulin resistance and that it modifies insulin signaling by targeting the degradation of the insulin receptor β-subunit and of IRS1 by its ubiquitin E3 ligase activity [27]. Recently, the same group reported that MG53 is a myokine/cardiokine secreted from striated muscles in response to high glucose or insulin in both rodents and humans [26]. Further, the serum level of MG53 is upregulated in obesity and T2DM, and administration of MG53 was found to inhibit the insulin response in multiple organs.…”
Section: Inhibitory Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM72, which remarkably expressed in skeletal and heart muscles, is a protein implicated in membrane repairment [ 22 , 23 ]. Considering that DMD disease manifests as membrane impairment, we explored how TRIM72 expressed in mdx mice.…”
Section: Resultsmentioning
confidence: 99%
“… 28–30 Cardiac-specific transgenic expression of MG53 induces severe diabetic cardiomyopathy in mice, accompanied by insulin resistance, increased lipid accumulation, myocardial hypertrophy, fibrosis, and cardiac dysfunction, 31 whereas others claimed that it has therapeutic applications, such as protecting injured mitochondria and inducing muscle regeneration. 32 , 33 Mitophagy ubiquitin ligases appear to have complex functions, and a single ligase may not modulate every form of mitophagy, but the process of mitophagy and the formation of phagosomes are likely mediated and regulated by networks of these proteins.…”
Section: Pink1 and Parkinmentioning
confidence: 99%